Anti-inflammatory effect of cortistatin in rat endotoxin-induced uveitis model - Balbaba, Mehmet; Dal, Ali; Colakoglu, Neriman; Bulmus, Ozgur; Ulas, Fatih; Yildirim, Hakan; Eroksuz, Yesari (Wolters Kluwer Medknow Publications, 2020)
Purpose: To evaluate the anti-inflammatory effect of cortistatin (CST) in endotoxin-induced uveitis (EIU) model and to compare the results with corticosteroid treatment. Methods: A total of 35 healthy Wistar albino rats were randomly divided into five groups. EIU was induced by a single subcutaneous injection of lipopolysaccharide (LPS). Group I received intraperitoneal (ip) normal saline (NS), Group II received ip 150 mu g LPS plus NS, Group III received ip 150 mu g LPS plus 250 mu g/kg CST, Group IV received ip 150 mu g LPS plus 1mg/kg dexamethasone, and Group V received ip 250 mu g/kg CST only. The aqueous humor was collected 24 h after injection and the infiltrating cells were determined. Moreover, histopathological and immunohistochemical examinations were also performed. Results: The clinical score and infiltrated cell count were reduced in Groups III and IV compared with Group II (P < 0.001). The pathological findings of Groups III and IV were significantly reduced compared with Group II (P < 0.001). These findings were similar between Groups III and IV (P = 1.000). Tumor necrosis factor-alpha (TNF-alpha) and interleukin 1 beta (IL-1 beta) immunoreactivity in the ciliary body of Group III and Group IV were significantly reduced compared with Group II (P < 0.001). TNF- and IL-1 beta immunoreactivity in the ciliary body of Group III and Group IV were similar compared with Group I and Group V (range of P values was 0.539-0.958). Conclusion: CST administration as a therapeutic agent might ameliorate the severity of intraocular inflammation in uveitis patients. In conclusion, effect of CST and dexamethasone in EIU model was comparable.
Keywords: Cortistatin; endotoxin-induced uveitis; interleukin-1; tumor necrosis factor-alpha